Building a Mosque's Competitive Advantage through the Management of Imams of Mosque - Ifansyah, M. Syukur; Thoha, Ahmad Faiz Khudlari; Gunawan, Reka (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
Like business enterprises, mosques and other nonprofit organizations also need to have a vital source of competitive advantage to increase their worshippers' uniqueness and attractiveness. If it can be adequately managed, imam masjid can be one of the uniqueness and continuing excellence for the mosque. One of the best practices in managing mosque’ imams as a competitive advantage is Masjid Raya Hubbul Wathan Islamic Center in West Nusa Tenggara. This research examines differentiation strategies in managing imams at Masjid Raya Hubbul Wathan Islamic Center in West Nusa Tenggara and how imams in the mosque can be a source of sustainable excellence and not only temporary. This research was conducted using qualitative methods with a case study approach. The collected data is analyzed descriptively based on the theory of competitive advantage, differentiation, and the VRIO framework. Among the critical findings in this study is the differentiation strategy in the management of imams at Masjid Raya Hubbul Wathan Islamic Center in West Nusa Tenggara carried out by: (1) the existence of a measurable and selective imam recruitment process; (2) the availability of competent priests with extensive and varied numbers; (3) involvement of international priests; and (4) the existence of a system of appreciation, improvement, empowerment of good mosque imams.